POTENSI PANTAI BISKI MENJADI OBJEK WISATA BAHARI DI KEPENGHULUAN PASIR LIMAU KAPAS KECAMATAN PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR PROVINSI RIAU - Nuraini "; Andi M.Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Biski beach has the potential of a wider beach with views of mangrove trees, mangrove trees. This study aims to determine: (1) To know the potential of marine tourism biski beach in Kepenghuluan Pasir Limau Kapas; (2) To know how the potential of the beach biski become a marine tourism object in kepenghuluan of lime sand Cotton.This research uses qualitative method with descriptive approach, research subject is Tourism Department, local community leader, Kepenghuluan Pasir Limau Kapas, and additional informant, that is Visitor. Data collection conducted, that is by document study, observation, depth interview. Analysis of data used in this study, namely data reduction, data presentation, conclusion drawing.The results showed that Biski Beach has potential, ie a wider beach with a view of mangrove trees. Some dead mangrove trees are not leafy and only have twigs, this beautiful beach scene makes us taste in the "Japanese Sakura Country". Waves of sea water and animals such as monkeys, birds and others also come decorate and color the panorama of Biski Beach in Kepenghuluan Pasir Limau Kapas. In Kepenghuluan this has a high social spirit characterized by the frequent community doing mutual cooperation. The conclusion of this research is Biski Beach With all the potential possessed by kepenghuluan of lime cotton, especially the potential of biski beach tourism object, biski beach tourism object is feasible to be developed into a tourist attraction by utilizing its own potential.Keywords: Biski Beach Potential, Marine Tourism, Kepenghuluan Pasir Limau Kapas